Theological reflection: Moving from the implicit to the explicit - Ault, Nancy (Pacifica, 2013)
During the late 20th and early 21st centuries, religion and theology have become increasingly separated from spirituality and affective experience in westernised societies. In addition to this rift, the body is frequently seen as marginal to spiritual life. The implications of these divisions for students engaging in theological reflection can be observed in reflections that are overly intellectualized or conversely overly emotional and lacking theological depth. In this article, it is suggested that through a balanced attending to bodily awareness, the recognizing and naming of emotions and the exploring of theological questions, theological reflection can offer a supporting framework in which theology and spirituality can be held together in partnership rather than as separate enterprises. If there is a playful and creative openness to reflection as an integrative praxis at risk of encountering the unexpected then the process of theological reflection can provide an opportunity for transformative learning.